Online Privacy, Young People, and Datafication: Different Perceptions About Online Privacy Across Antigua & Barbuda, Australia, Ghana, and Slovenia - Rys Farthing; Katja Koren Ošljak; Teki Akuetteh; Kadian Camacho; Genevieve Smith-Nunes; Jun Zhao (Social Media + Society, 2024)
Children and young people’s online privacy is increasingly challenged by the datafication of the digital world, and this is an increasingly important area of policy concern. Understanding what young people understand online privacy to be, and what they want done to protect it, is key to creating effective and rights-realizing policy responses. This article explores young people’s perceptions across four countries and finds they have nuanced understandings about online privacy and clear, robust ideas about how to improve it. Context mattered, and their online privacy concerns and ideal protections were often informed by their socio-political context and awareness of and trust in datafication.